Capital Gains Realizations of the Rich and Sophisticated - Auerbach, Alan J; Siegel, Jonathan M (American Economic Review, 2000)
This paper attempts to bring theoretical and empirical research on capital gains realization behavior closer together by considering whether investors who appear to engage more in strategic tax avoidance activity also respond differently to tax rates. We find that such investors exhibit significantly smaller responses to permanent tax rate changes than other investors. Put another way, a larger part of their response to capital gains tax rates reflects timing, consistent with their closer adherence to tax avoidance strategies emphasizing arbitrage based on tax rate differentials. This finding holds for two alternative specifications of realization behavior, one of which suggests larger permanent responses to capital gains tax rates than those of previous panel studies.